2021
DOI: 10.37360/blacpma.21.20.6.47
|View full text |Cite
|
Sign up to set email alerts
|

In vitro pharmacological attributes and metabolite’s fingerprinting of Conocarpus lancifolius

Abstract: Search for safe antioxidants and novel nutraceuticals urged to evaluate the antioxidant, anti-acetylcholine esterase and anti-lipoxygenase activity of various leaf extracts of Conocarpus lancifolius. Extraction was optimized from freeze dried plant extracts quenched with liquid nitrogen using water, ethanol, methanol, hexane, ethyl acetate and chloroform. Maximum extract yield, total phenolic contents and total flavonoid contents were obtained in case of ethanolic extraction. The highest 2,2-diphenyl-1-picrylh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…In addition, exposure to acute NS elevates the AChE activity in a compensatory way in the hippocampus, which is attributed to anxiety, depression-like behaviors and memory deficits in stressed animals [ 4 , 119 , 120 ]. It was stated previously that ethanolic and water extracts of C. lancifolius leaves displayed substantial AChE inhibitory potential [ 29 ]. In the present study, we verified for the very first time that CLAE has moderate AChE inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, exposure to acute NS elevates the AChE activity in a compensatory way in the hippocampus, which is attributed to anxiety, depression-like behaviors and memory deficits in stressed animals [ 4 , 119 , 120 ]. It was stated previously that ethanolic and water extracts of C. lancifolius leaves displayed substantial AChE inhibitory potential [ 29 ]. In the present study, we verified for the very first time that CLAE has moderate AChE inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, therapeutic approaches strengthening the antioxidant enzyme potential, including catalase (CAT), glutathione peroxidase (GPx) and superoxide dismutase (SOD), reducing the malondialdehyde (MDA) level (main end-product of lipid peroxidation), scavenging the other free oxygen species or regularizing the AChE function in different brain areas may have a precautionary effect against NS-induced anxiety, depression and cognitive failure [ 8 , 127 ]. Antioxidants are substances that can scavenge excessively produced ROS and therefore mitigate the OS burden [ 29 ]. Recent experimental approaches have shown that phenolics, particularly flavonoids, alkaloids, tannins, coumarins and lignans, are among the most effective antiradicals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pengukuran kadar GDP tikus menggunakan metode Glucose Oxidase-Peroxidase Aminoantipyrine (GOD-PAP) yang dimana merupakan metode paling sering digunakan di laboratorium. 23 Sampel darah diambil melalui sinus retro-orbitalis, tikus dipegang dengan ibu jari dan diberikan tekanan vena jugularis di bagian caudal mandibula, lalu tabung mikrohematokrit dimasukkan pada ujung mata bagian depan untuk penetrasi conjunctiva orbitalis agar terjadi ruptura sinus retro-orbitalis, bila sinus atau plexus telah ruptur maka darah akan mengalir melalui tabung darah diambil 2 ml. 24 Alat untuk menguji kadar GDP pada tikus dapat menggunakan spektrofotometer UV-VIS AMV11 dengan spesifikasi panjang gelombang 190 -1100 nm, akurasi panjang gelombang ± 0,5 nm, akurasi fotometrik ± 0,5 persen T dan dimensi alat 460 x 360 x 225 mm.…”
Section: Metode Penelitianunclassified